(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
It's not an easy effort to include climate change into literature. To explore how global warming impacts human character, the future, imagined landscapes, the political realm, or culture, the novel must bring fact into dialogue with fiction. The way that science is incorporated into fiction is a deeper issue that lies beneath all of these decisions. Writers exploit different strategies to reach thisgoal